Identification of Hydrochemical Function and Behavior of the Houzhai Karst Basin, Guizhou Province, Southwestern China. (13th March 2018) - Li, Xian; Wang, Yanqiao
Abstract : Due to the difference of geomorphology and the development of fractures, the hydrochemical function and behavior appear to be complex. Variations of karst water conductivity can reflect the contribution of different runoff sources and thus indirectly reflect the development characteristics of conduits and fractures. Taking Houzhai karst system (southwestern China) as a case study, the frequency distribution curves of karst water conductivity were decomposed by Gaussian Mixture Analysis to identify the runoff components of different karst landform. The dominant runoff types had been distinguished, and the relative contribution of the different water types had been investigated. The results showed that the karst flow types were slope flow, rapid fracture flow, and slow fracture flow. Rapid fracture flow was the major recharge type of Houzhai karst water system. Slow fracture flow in the downstream area accounted for a larger proportion than that of the upstream area. The relative contribution of the different runoff components showed that the upstream area was a rapid flow area of conduit structure with low storage capacity, the downstream area was an aquifer spatial structure of netted fissure conduit with high storage capacity, and the midstream area was a transitional zone between the upstream and downstream area.